494 A Qualitative Analysis of Barriers and Facilitators to Documentation in Community Pharmacy Electronic Patient Records in Ireland. (13th April 2023) - Murphy, K; Kelly, L
Abstract: Introduction: An Electronic Patient Record (EPR) is a repository for medical and pharmaceutical information in Community Pharmacies. Studies have shown that almost three-quarters of EPRs have at least one discrepancy between information documented in the EPR and patient-reported information, while drug therapy alerts failed to appear for about one-third of patients due to a lack of documented medical and/or pharmaceutical data(1). More complete documentation in Community Pharmacy EPRs could improve the quality of patient care provided. To-date, there is limited research available concerning documentation in Community Pharmacy EPRs in Ireland. Aim: The aim of this study was to identify the key barriers and facilitators to documentation in Community Pharmacy EPRs in Ireland. Methods: Registered Community Pharmacists were invited to participate via email using convenience sampling. Participant Information Leaflet and Consent Forms were emailed to each community pharmacist at least 24 hours prior to each interview explaining why and how the research study was being carried out. Semi-structured interviews were carried out until theoretical saturation was reached. 11 interviews were conducted virtually through the UCC-approved Google Meet and two interviews took place by telephone. Finally, the audio recordings from interviews were transcribed verbatim and then analysed using Braun and Clarke's thematic analysis(2). Results: A total of 13 Community Pharmacists were interviewed. The majority of participants were female (n=9), supervising pharmacists (n=8), and had greater than 10 years community pharmacy experience (n=8). All pharmacists document the basic personal and clinical patient information necessary for safe supply as advised by the Pharmaceutical Society of Ireland (PSI), but most did not document additional information such as morbidities or over-the-counter medication. The key barriers identified were accessing information from Healthcare Professionals and patients, software limitations and time. The key facilitators identified were Standard Operating Procedures and a centralised Electronic Health Record system. Most pharmacists were willing to participate in a training program to enhance documentation practices. Conclusion: This study highlighted the key barriers that need to be addressed to facilitate more complete documentation. A limitation is the potential for social desirability bias in participants in minimising the extent of negative documentation practices. Comprehensive interventions combining more guidance from the PSI, webinars on utilising the EPR, and software modifications could encourage practice change. Future research should evaluate the impact of these measures on documentation completeness in Community Pharmacy EPRs in Ireland. References: 1. Floor-Schreudering A, Heringa M, Buurma H, Bouvy ML, De Smet PAGM. Missed drug therapy alerts as a consequence of incomplete electronic patient records in Dutch community pharmacies. Ann Pharmacother. 2013;47(10):1272–9. 2. Braun V, Clarke V. Using thematic analysis in psychology. Qual Res Psychol [Internet]. 2006 [cited 2022 Apr 21];3(2):77–101. Available from: https://www.tandfonline.com/doi/abs/10.1191/1478088706qp063oa